Analisis Pengaruh Kebijakan Program Keluarga Harapan (PKH) Terhadap Kemiskinan Di Provinsi Gorontalo - Ahmad, Ayub; Arham, Muhammad Amir; Djuuna, Rifi Fazrina (Cattleya Darmaya Fortuna, 2025)
This study aimed to discover the proper implementation of PKH on poverty in Gorontalo Province. This quantitative research used secondary data from Statistics of Gorontalo through Susenas KOR&KP 2019-2024. This study addressed the issue of poor families encountering education, health, and social welfare problems in Gorontalo Province and involved 5.168 beneficiary families. Based on analysis, the PKH had no negative impact on poverty in Gorontalo Province although it only fulfilled the temporary or short-term necessities of a family.